Bacterial Diversity and CAZyme Potential Revealed in Pandanus Rich Thermal Spring Cluster of India: A Non-cultivable 16S rRNA Sequencing Approach - Dixit, Sangita; Gaur, Mahendra; Subudhi, Enketeswara; Sahoo, Rajesh Kumar; Dey, Suchanda; Mahapatra, Lakshmi Datta; Mandal, Surajit De; Senthil Kumar, Nachimuthu; Anirudh, Hardik (Frontiers in Microbiology, 2021)
In the present study, we explored four different geothermal spots of the Deulajhari spring cluster at a proximity of 10–20 meters with temperatures of 43 to 65°C to unravel their genesis, bacterial diversity and CAZyme potential. However, minor variations in physicochemical properties; TOC, sodium, chloride, zinc and nitrate were observed, including the pH of the spring openings. Illumina based amplicon sequencing revealed Firmicutes, Proteobacteria and Chloroflexi as the major bacterial phylum with higher abundance in the DJ04 sample. The alpha diversity of all the springs was almost same, whereas beta diversity revealed variations in the degree of uniqueness of OTUs at different temperatures. Statistical analysis established a positive correlation between sulfur content with Heliobacterium, Thermodesulfovibrio, Thermodesulfobacterium and Herpetosipho as well as TOC and HCO3 with Thermoanaerobacter, Desulfovibrio, Candidatus solibacter and Dehalogenimona. The major hydrocarbon family genes and Carbohydrate Active Enzyme pathways were predicted to be highest in DJ04 with elevated concentrations of HCO3 and TOC. Higher homogeneity in geo-physicochemical and microbial features direct the possibility of the common origin of these springs through plumbing systems. However, the minor variations in diversity and functionality were due to variations in temperature in spring openings through the mixing of subsurface water contaminated with carbohydrates from leaf biomass litter. Functional characterization of the thermophilic bacteria of this spring provides essential scope for further industrial applications. The biogeochemical reasons hypothesized for the genesis of unique multiple openings in the cluster are also of interest to conservation scientists for taking measures toward necessary laws and regulations to protect and preserve these springs.